High-speed running distance and frequency in football training: When and how are they stimulated in a microcycle? - Marín, K.; Castellano, J. (International Journal of Sports Science & Coaching, 2023)
The aims of this study were to describe the distribution of the distance and frequency of the high-speed running performed by professional players during the training process, taking into account the duration of the microcycle (Mi) composed of 4, 5, 6 and 7 days between matches (MD). Total distance at high speed (HSR, >21 km·h-1, in m), at very high-speed running (VHSR, >24 km·h-1, in m) and sprint (SPR, >27 km·h-1, in m) were recorded, in terms of distance (d) and frequency (n) during training sessions. Training data were obtained using global positioning technology from 23 professional football players belonging to the first team of the Spanish La Liga club during the 2017/18 season (n = 28 microcycles). There were no significant differences in volume (distance and frequency) of the different locomotive demands (LD) when Mi accumulated more days. Regardless of the duration of the Mi, the central days (MD-5, MD-4 and MD-3) accumulated more stimulus in HSR, VHSR and SPR compared to the post sessions (MD-6 and MD-7) and pre-match (MD-2 and MD-1) where the MD-2 was the day that required the least stimuli from the players (p < 0.05). The Mi7 presented significantly higher external load values in the MD-5 and MD-4 compared to the Mi5 and Mi4, where the MD-3 was the day that received the greatest stimulation in the locomotive demand (p < 0.01). The data demonstrate that the LD (HSR, VHSR and SPR), accumulated greater stimulus in the central days of Mi, far from the previous competition, favoring an optimal recovery without compromising performance for the next game